Diabetes control in public assistance recipients and free/low-cost medical care program beneficiaries in Japan: a retrospective cross-sectional study - Daisuke Nishioka; Mitsuhiko Funakoshi; Seiji Haruguchi; Sakae Yonemura; Takashi Takebe; Misato Nonaka; Sanae Iwashita (BMJ Publishing Group, 2024)
Introduction Previous research has highlighted the association between socioeconomic factors and diabetes management. This study aimed to elucidate the blood glucose control status among individuals with low income (ie, recipients of public assistance (PARs) and free/low-cost medical care (FLCMC) programme beneficiaries) and to investigate the effects of public subsidies for medical expenses on treatment adherence among low-income patients with diabetes.Methods We conducted a secondary analysis of medical records from 910 outpatients with diabetes who underwent pharmacological treatment for >90 days. Data on predictive variables, such as glycated haemoglobin (HbA1c) level and control variables, including sex, age and insurance type, were obtained retrospectively. The HbA1c levels among public health insurance (PHI)-only beneficiaries, FLCMC programme beneficiaries and PARs were compared using logistic regression analysis.Results The analysis included 874 individuals, among whom the majority were men (61.7%) and aged≥65 years (58.4%). Logistic regression analysis revealed that among individuals aged ˂65 years, the adjusted ORs for HbA1c levels above 9% were significantly higher in FLCMC programme beneficiaries (OR=5.37, 95% CI: 2.23 to 12.82) and PARs (OR=5.97, 95% CI: 2.91 to 12.74) than in PHI-only beneficiaries. Among patients aged ˂65 years with HbA1c levels above 7%, the adjusted OR was significantly higher in FLCMC programme beneficiaries (OR=3.82, 95% CI: 1.65 to 10.43) than in PHI-only beneficiaries. Additionally, the adjusted OR was significantly higher in FLCMC programme beneficiaries aged ˂65 years (OR=2.57, 95% CI: 1.02 to 7.44) than in PARs.Conclusions This study highlights the predictive value of public assistance or the FLCMC programme for poor blood glucose control and suggests the inadequacy of current medical expense subsidies to eliminate health disparities in diabetes control.